Factors affecting school failure by using factor analysis- Afield study of a sample of high school students in Oran - Belabbes , Fadela; Rachedi , Khadra (Al-Jamie Journal In Psychological Studies and Educational Sciences, 2022)
The present study aimed to determine the factors affecting school failure and arrange them according to their importance using the factor analysis method and based on the data of a questionnaire drawn from a field study that included 1000 students who failed in a number of secondary schools in Oran. The study concluded with the conclusion of 8 factors the first and most important of which is contribution to school failure is the environment. The family which included 5 variables, was the most common of family problems and the relationship between parents. The other factors were arranged as follows: mother’s characteristics, family income, hobby, father’s characteristics, number of siblings, housing conditions, transportation to the institution and finally the school environment.